The Effect of Bamboo Charcoal Micro Particles Application on the Comfort Properties of Woven Fabric - Matthew Brendon Foo; Siti Hana Nasir (Progress in Engineering Application and Technology, 2024)
This research delves into bamboo as a sustainable substitute for conventional materials, emphasizing its swift growth and environmental consciousness amid diminishing finite resources. Bamboo charcoal, derived through carbonization, is known for its distinctive qualities, particularly its ability to eliminate microorganisms causing odors and stains in textiles. This study investigates the impact of applying bamboo charcoal microparticles as a coating on woven fabrics, evaluating their influence on comfort qualities and fabric properties. The coating solution, comprising 2% bamboo-derived activated carbon, 2% flexible acrylic binder, 1% wetting agent, and 2000 ml of ionized water, was applied using the pad-dry-cure method. SEM analysis showcased the exceptional durability of bamboo charcoal microparticles on fabric fibers. AATCC Test Method 61-2020 2A, Rapid Sand Washer, and wicking tests assessed the coating’s durability, revealing a significant increase in reduction percentages after prolonged washing. This underscores the adverse impact on wicking properties, emphasizing the need for sustainable fabric solutions.